2021
DOI: 10.3390/ma14051318
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Additively Manufactured Tools in Abrasive Machining—A Literature Review

Abstract: High requirements imposed by the competitive industrial environment determine the development directions of applied manufacturing methods. 3D printing technology, also known as additive manufacturing (AM), currently being one of the most dynamically developing production methods, is increasingly used in many different areas of industry. Nowadays, apart from the possibility of making prototypes of future products, AM is also used to produce fully functional machine parts, which is known as Rapid Manufacturing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 97 publications
(129 reference statements)
0
8
0
Order By: Relevance
“…Suryawanshi et al reported similar outcomes for AlSi12 as well. The elongated grain structure of AlSi10Mg and Al-Mg-Cu, on the other hand, has a dominant {1 0 0} texture along the build direction, as shown by Takata et al and Zhang et al [208][209][210][211][212][213][214]. These variances are attributed to variations in the melt pool shape geometry and consequently thermal gradients, while not being stated directly.…”
Section: Crystallographic Texture Of Laser-based Additvely Manufactur...mentioning
confidence: 98%
See 1 more Smart Citation
“…Suryawanshi et al reported similar outcomes for AlSi12 as well. The elongated grain structure of AlSi10Mg and Al-Mg-Cu, on the other hand, has a dominant {1 0 0} texture along the build direction, as shown by Takata et al and Zhang et al [208][209][210][211][212][213][214]. These variances are attributed to variations in the melt pool shape geometry and consequently thermal gradients, while not being stated directly.…”
Section: Crystallographic Texture Of Laser-based Additvely Manufactur...mentioning
confidence: 98%
“…Inverse pole figure orientation map displaying the elongated grain structure's predominately {1 0 0}orientation along the build direction. Additionally, the orientation map reveals a finer grain structure at the melt's sides and top, but there is no clear dominating orientation[208,211].…”
mentioning
confidence: 96%
“…It is believed that the methodical distribution of grits on wheel surfaces can increase wheel life and improve surface roughness and eventually the grinding efficiency. 197 Qiu and Huang 198 fabricated the controlled arrangement of grinding wheels with the help of light resins-based AM technique which is shown in Figure 25. The FEM simulation of the fabricated wheel is performed to know the MRR, which is further verified by conducting the experiments.…”
Section: D Printing Of Grinding Wheelsmentioning
confidence: 99%
“…Machining ceramic materials is still a big challenge for the industry [16]. Deja et al pointed out [17] that fabricating abrasive tools by additive manufacturing (AM) processes is one of the promising directions in the development of novel finishing processes. This is due to the fact that AM technologies offer new opportunities in the fabrication of parts with strictly defined inner and outer geometries [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The SLS method used to produce lapping tools has rarely been studied, as indicated by Deja and Zieliński [17]. Herein, a prototype lapping plate was prepared by the SLS method and applied in the flat-lapping of technical ceramics Al 2 O 3 .…”
Section: Introductionmentioning
confidence: 99%